Adolescent fertility in the Cienfuegos province. From 2012 to 2021 - Yadira Sarrìa Zerquera; Yenisvel Yut vidal (Medisur)
Foundation: the adolescent fertility study, as well as its change over time, is of great importance, since it allows us to show its progress or setbacks. Objective: characterize the fertility behavior in the Cienfuegos province. Methods: descriptive, cross-sectional study, which had as the research universe the entire female population aged 15-49 years old of Cienfuegos from 2012 to 2021, as well as the births that occurred in this age group, in addition to those of 15 years old younger mothers. The analyzed indicators were: specific fertility rate, emphasizing the adolescent fertility rate (15-19 years old), average age and weight of the adolescent fertility rate to total fertility. The data were obtained from the National Office of Statistics and Information statistical yearbooks, of the National and Provincial Public Health Ministry Directorate of Statistics. Results: the adolescent fertility rate presents slight oscillations, going from 46.7 children per woman in 2012 to 45.4 in 2021. The age group with the highest fertility is 20-24 years old, the average age is in the age group 25-29 years old and the municipalities with the greatest weight in total fertility are Abreus and Aguada de Pasajeros. Conclusions: the adolescent fertility rate shows resistance to decline, a behavior that demonstrates the need to emphasize sexual education policies and strategies for the most vulnerable age groups within the reproductive group.